Affective Neuroscience: The Suitability of a Web App to Monitor Affective States at Work - Manfredi, Paola; Massardi, Elena (Frontiers in Psychology, 2021)
Affective neuroscience has had declinations in many areas but still little use in the work, also due to the lack of a smart tool. In this paper is presented a new instrument – a web-app based on the conceptual frame of affective neuroscience, and in particular on Panksepp's 7 basic emotion systems. The theoretical framework, the perspective of intervention, and the characteristics of the instrument are described. We also present the results of its application in a company in Northern Italy to test the functioning of working teams, through the recording of basic affective states. It is 488 recordings, which, together with the related tags, have enabled to work out profiles of the teams analysed, and to identify areas of possible interventions to be drawn up. The data seem very encouraging.